CONTENT MARKETING SEBAGAI STRATEGI MERAIH ENGAGEMENT TINGGI MELALUI MEDIA SOSIAL: (Studi kasus pada Instagram @harian.disway Surabaya) - Mahendra Syahputra, Dandy; Widhiandono, Doan (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Engagement is very important because the more interactions that occur on a post that is uploaded, the higher the response and interest it will get from the audience. The aim of this research is to understand, analyze and describe the strategies used by the Harian Disway Surabaya to get high engagement on every Instagram post. The method used is qualitative, with a type of descriptive research that systematically describes the facts or characteristics of the object being studied carefully and factually. The data used comes from primary and secondary data obtained through surveys, observations, interviews, documentation, and literature reviews from previous related research. The results of this research is Harian Disway has utilized the theory of content marketing strategy well to create high engagement on its Instagram social media. There are also other factors that make @harian.disway Instagram content engagement is high, namely Harian Disway's upload speed compared to other media. Keyword: Content marketing, strategy, engagement, Instagram, Harian Disway.